2005
DOI: 10.4040/jkan.2005.35.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Attitudes to Research Among Nurses in One Hospital in Korea

Abstract: There is an urgent need to promote both the ability and environment for clinical nurses to actively participate in research. As the majority of nurses had little experience and low confidence in research and perceived many barriers, this promotion can be accomplished by enhancing their confidence in research through continuing education and by gradually eliminating the barriers to research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Barriers and socio-demographic factors influencing nurses participation in and utilisation of clinical research in practice : The study revealed that insufficient time for nurses to read articles was associated with nurses' participation in research as it recorded a P-value of 0.04 at a 95% confidence interval. As studies from both Zimbabwe [ 17 ] and Singapore [ 18 ] show similar results, inadequate time may be a characteristic of nurses' work situation. Moreover, nurses' perception about research as not a nursing role was expressed in the qualitative interviews and also found to be statistically significant with a P-value of 0.04.…”
Section: Discussionmentioning
confidence: 73%
“…Barriers and socio-demographic factors influencing nurses participation in and utilisation of clinical research in practice : The study revealed that insufficient time for nurses to read articles was associated with nurses' participation in research as it recorded a P-value of 0.04 at a 95% confidence interval. As studies from both Zimbabwe [ 17 ] and Singapore [ 18 ] show similar results, inadequate time may be a characteristic of nurses' work situation. Moreover, nurses' perception about research as not a nursing role was expressed in the qualitative interviews and also found to be statistically significant with a P-value of 0.04.…”
Section: Discussionmentioning
confidence: 73%
“…Hence, nurse educators should consider devising educational strategies to suit nurses' preferred learning styles especially when teaching research because it is a specialised topic and nurses have very limited experience and confidence to conduct research 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most nurses preferred skill-based workshops (61%) to learn research compared to online learning (25%) despite the relatively younger nurses in this study sample, this could be due to the 'hands-on,' contextualised approach to learning in nursing that is aligned with clinical practice that was identified in a recent study 20 done with a group of final semester nursing students. Hence, nurse educators should consider devising educational strategies to suit nurses' preferred learning styles especially when teaching research because it is a specialised topic and nurses have very limited experience and confidence to conduct research 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Pôde confirmar-se durante a investigação que os indivíduos com um grau académico superior consideram que o processo de investigar é relativamente mais simples, comparado com graus académicos mais baixos (Pimenta, 2011;Kang, 2005).…”
Section: Discussionunclassified